Learning React Native : building mobile applications with Javascript - Eisenman, Bonnie, ....- (Beijing : O'Reilly, 2016)
Get a practical introduction to React Native, the JavaScript framework for writing and deploying fully featured mobile apps that look and feel native. With this hands-on guide, you'll learn how to build applications that target iOS, Android, and other mobile platforms instead of browsers. You'll also discover how to access platform features such as the camera, user location, and local storage. With code examples and step-by-step instructions, author Bonnie Eisenman shows web developers and frontend engineers how to build and style interfaces, use mobile components, and debug and deploy apps. Along the way, you'll build several increasingly sophisticated sample apps with React Native before putting everything together at the end.
Keywords: Mobile apps; JavaScript (Computer program language).